Health Self-Management Behaviors as a Bridge Between Electronic Health Literacy and Health-Related Quality of Life: Cross-Sectional Study From China - Meihui Zhang; Shunyu Tao; Xin Ge; Hongying Zhang; Zhongqing Xu; Ruijie Gong; Yujie Liu; Chen Xu; Suping Wang; Yong Cai (Journal of Medical Internet Research)
Abstract BackgroundElectronic health literacy (eHL) has been increasingly associated with health-related quality of life (HRQoL). However, the underlying mechanisms, especially in the general population, remain insufficiently explored. ObjectiveThis study aimed to investigate the mediating role of health self-management behaviors (HSMB) in the relationship between eHL and HRQoL. MethodsA cross-sectional study was conducted in Shanghai, China, from October to December 2022. Participants were recruited via convenience sampling from 7 community health service centers. Data were collected through an online survey platform Wenjuanxing. Validated scales, including the eHL Scale, the adults’ health self-management skill rating scale, and the 12-item short form health survey were used to measure eHL, HSMB, and HRQoL, respectively. The HRQoL was summarized into the physical component summary (PCS) and the mental component summary (MCS). Correlation analysis, multivariate linear regression with stepwise backward selection, and mediation analysis were performed to explore the relationships among eHL, HSMB, PCS, and MCS, with adjustments for sociodemographic and health-related covariates. ResultsAmong the 2364 participants recruited from urban, periurban, and rural areas, eHL scores varied significantly by demographic characteristics. Positive correlations among eHL, HSMB, PCS, and MCS were observed, with Spearman correlation coefficients ranging from 0.24 to 0.46 (PR2PR2PcPcPc’Pc’P ConclusionsThis study demonstrated a positive association between eHL and HRQoL, with HSMB acting as a partial mediator among the general population in Shanghai. Targeted interventions should be implemented to improve eHL and HSMB.